Peningkatan Kesadaran Kenakan Masker Melalui Adu Video Kreatif Yel Pakai Masker dalam Mencegah Transmisi Virus Corona - Hidayah, Seventina Nurul; Harnawati, Riska Arsita; Umriaty, Umriaty; Izah, Nilatul; Qudriani, Meyliya; Nisa, Juhrotun (Universitas Nusantara PGRI Kediri, 2021)
The case of the Covid-19 corona virus infection in Central Java is in a critical situation because it is ranked number 3 in Indonesia. The spread of cases outside the cluster was due to the lack of discipline by the community in wearing masks. Kudaile is one of the sub-districts located in the Slawi sub-district with a fairly dense population so it is very vulnerable to the spread of Covid-19 if it is not balanced with public awareness of using masks appropriately. The service activities that we will carry out are creative competitions / fights using masks in Kudaile Village, Slawi District. With this service activity, it is hoped that the public will be aware of the importance of using masks appropriately to prevent transmission. The result of this community service is the collection of videos of yells wearing masks which prove that the public is increasingly aware of how to use masks and the discipline of using masks is getting tighter to prevent the transmission of the spread of the corona virus.